Adolescents’ psychological health during the economic recession: does public spending buffer health inequalities among young people? - Rathmann, Katharina; Pförtner, Timo-Kolja; Osorio, Ana M.; Hurrelmann, Klaus; Elgar, Frank J.; Bosakova, Lucia; Richter, Matthias (BMC public health, 2016)
Background Many OECD countries have replied to economic recessions with an adaption in public spending on social benefits for families and young people in need. So far, no study has examined the impact of public social spending during the recent economic recession on health, and social inequalities in health among young people. This study investigates whether an increase in public spending relates to a lower prevalence in health complaints and buffers health inequalities among adolescents. Methods Data were obtained from the 2009/2010 “Health Behaviour in School-aged Children (HBSC)” study comprising 11 – 15-year-old adolescents from 27 European countries ( N = 144,754). Socioeconomic position was measured by the Family Affluence Scale (FAS). Logistic multilevel models were conducted for the association between the absolute rate of public spending on family benefits per capita in 2010 and the relative change rate in family benefits (2006–2010) in relation to adolescent psychological health complaints in 2009/2010. Results The absolute rate of public spending on family benefits in 2010 did not show a significant association with adolescents’ psychological health complaints. Relative change rates of public spending on family benefits (2006–2010) were related to better health. Greater socioeconomic inequalities in psychological health complaints were found for countries with higher change rates in public spending on family benefits (2006–2010). Conclusions The results partially support our hypothesis and highlight that policy initiatives in terms of an increase in family benefits might partially benefit adolescent health, but tend to widen social inequalities in adolescent health during the recent recession.